Politics, policy, and public options - Sitaraman, Ganesh; Alstott, Anne, 1963- (Cambridge, United Kingdom ; New York : Cambridge University Press, 2021)
"A public option is a government-provided social good that exists alongside a similar privately provided good. While the public option is typically identified with health care policy, public options have been a longstanding feature of American life in a variety of sectors, ranging from libraries to swimming pools. Public schools, for example, coexist alongside private schools. However, there is surprisingly little research on "public options" as a general category. Rather, over the last few decades, considerable scholarly and popular efforts to ensure access to important social goods have focused on market subsidies (like vouchers) or privatization - which both face increasing criticism. Uniting scholars from across disciplines, this volume delves into the theory of the public option, explores several important case studies, and shows how public options could be a corrective to the trend toward privatization and subsidies. This title is also available as Open Access on Cambridge Core"--
Introduction / Ganesh Sitaraman & Anne Alstott -- More than meets the eye : government social provision and the politics of "public options" / Mallory SoRelle & Suzanne Mettler -- The entrpreneurial state : socializing risks and rewards / Mariana Mazzucato & Henry Lishi Li -- Challenges in designing equitable public options / Anne Alstott & Ganesh Sitaraman -- What about private options / Jon D. Michaels -- The original - and still the best? : the health insurance public option and the politics of social reform / Jacob S. Hacker -- The irony of health care's public option / Allison K. Hoffman -- Promoting quality and equality through a public option in early childhood education and care / Kimberly J. Morgan -- Revamping public energy / Shelley Welton -- A public option in banking : postal banking / Mehrsa Baradaran.
Includes bibliographical references.
Keywords: Social legislation -- United States; Public-private sector cooperation -- Law and legislation -- United States